Solar water pump sizing tool for Nepal: user manual - Mali, S. S.; Gautam, K.; Verma, Shilp (Government of Nepal. Ministry of Energy, Water Resources and Irrigation. Alternative Energy Promotion Centre (AEPC), 2024)
Solar water pumps offer a sustainable solution for irrigation and drinking water in Nepal. Limited local technical know-how can hinder effective planning and budgeting for solar initiatives. To address this, IWMI collaborated with ICAR and GIZ-POSTED to jointly develop an Excel-based Solar Water Pump Sizing Tool for use in Nepal. The Beta version of tool is designed for the initial planning phase only (pre-feasibility) and specifically for the use by Alternative Energy Promotion Centre (AEPC) and local provincial government in Nepal. The tool enables quick, location-specific pre-feasibility assessments of system capacity and cost for both irrigation and drinking water needs. Building on a similar tool developed by IWMI and ICAR in India, the SWP Sizing Tool includes modules for water demand estimation, system sizing, and a bill of quantity. This User Manual walks through the architecture, instructions, and limitations of the tool. The summary report generated by the tool highlights key system features, costs, and a breakdown of the bill of quantity. It also includes what-if scenarios to allow optimization of the system capacity. The tool will support informed decision-making in the process of decentralized planning of solar investments in Nepal.